Determinants of early marriage incidence in adolescents in Rural West Kupang District, East Nusa Tenggara - Suci Aspriyanti Anwar; Mega Putri Amalanda Amalanda; Rani Kusumawardani; Qorinah Estiningtyas Sakilah Adnani; Chyntia Haryana (Science Midwifery, 2026)
Early marriage remains a major public health problem in East Nusa Tenggara (NTT), particularly in rural areas where local cultural practices have received limited quantitative investigation despite their potential influence on marriage decisions. This study aimed to identify the determinants of early marriage among adolescents in rural West Kupang District. This quantitative study employed a cross-sectional design involving 98 adolescents aged 15–19 years from two villages (Oenaek and Sumlili) selected using the Slovin formula. Data were analyzed using univariate, bivariate (chi-square), and multivariate (multiple logistic regression) analyses. The prevalence of early marriage was 27.6%. Bivariate analysis identified six factors significantly associated with early marriage (p < 0.05), while multivariate analysis showed that local cultural/customary perceptions (AOR = 6.1; 95% CI: 1.9–19.6; p = 0.002), poor reproductive health knowledge (AOR = 3.2; p = 0.036), and poor family economic status (AOR = 2.9; p = 0.049) were the dominant determinants. The novelty of this study lies in quantitatively examining the role of local cultural perceptions, including the belis tradition, together with socioeconomic and behavioral factors in a rural NTT setting. These findings provide evidence to support culturally sensitive policies, strengthen adolescent reproductive health education, and guide community-based interventions to prevent early marriage in rural areas.